RELATIONAL ENCOUNTERS WITH INDIGENOUS LITERATURES - Hanson, Aubrey Jean (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
This paper makes a case for attending to the resurgence of Indigenous literary arts in taking up the Truth and Reconciliation Commission of Canada’s Calls to Action in teacher education. I argue that Indigenous literary arts can help to foster relational understandings between readers and Indigenous communities: stories have the capacity to open up processes of relationship and responsibility. To develop this argument, I draw upon perspectives from teachers and from Indigenous writers, with whom I shared conversations on the question of why Indigenous literatures matter. Through an interpretive process of interweaving these perspectives, this article shows that Indigenous literatures can inspire and motivate educators to take on this work and learning despite its attendant challenges.